APPLICATION OF THE PENMAN-MONTEITH METHOD TO DETERMINE THE CROP WATER REQUIREMENTS - Arzita, Tasya Dyta; Nurhayati, Nurhayati; Gunarto, Danang (Jurnal Teknik Sipil, 2023)
Agricultural production is critical to meeting Indonesia's food demands. The water catchment area of Parit Keladi 1, located in Desa Parit Keladi, Kecamatan Sungai Kakap, Kabupaten Kubu Raya, Provinsi Kalimantan Barat, includes tidal swamp land that has a variety of plants. The Cropwat 8.0 Software will be used in this research to assess crop water needs. This research employs primary and secondary data, including soil samples, field cropping patterns, and plant hydration levels.The type of clay soil was silty, the field cropping pattern at the study site was paddy, and the height of the water puddle on paddy was 3 mm/day/ha, according to the findings of primary data analysis on soil sampling. The maximum water need for paddy was 5.90 mm/day/ha in March period 1, while the lowest water requirement was 0 mm/day/ha in October period 1. The maximum water need for citrus was 2.62 mm/day/ha in August for period 3, while the lowest water requirement was 0 mm/day/ha from October to December and May to June for period 1. In September Period 3, the crop water required in the Cropwat 8.0 Software was 32.2 mm/day/ha for ten days; however, the water level in the field was 3 mm/ha for one day in late September. Thus, the estimate of water demands for rice plants using the Cropwat 8.0 Program is valid.